Cu2O–ZnO heterojunction solar cell coupled to a Ni(OH)2-rGO-PPy supercapacitor within a porous stoneware tile. Issue 16 (November 2020) - Orozco-Messana, J.; Daly, R.; Zanchetta-Chittka, I.F.
Abstract: Coupling photovoltaic solar energy (PV) generation with its storage for full availability is a key challenge for sustainable PVs. Tile integration of both can turn buildings or other urban structures, onto autonomous power units for low consumption electronics, sensors, and different e-services, through film printed electronics, ubiquitously available for future smart cities, support the deployment of the internet of things, and closing the gap to net zero energy buildings. Starting from a porous stoneware tile, an electroless conductive Ni–Mo–P layer is the starting point for infiltrating on the connected porosity (3D free structure) of the tile thickness a nanostructured Ni(OH)2 -rGO-PPy composite acting as supercapacitor. On the open conductive surface an optimized p-Cu2 O/n-ZnO heterojunction was grown integrating a coupled charge-storage electrical circuit seamlessly on a commercial tile. The research presented on this paper has allowed the first experimental results of an autonomous, low-cost, energy supply system for future development of building integrated electronics.